The relationship between prospective teachers’ nutritional literacy and healthy lifestyle behaviors - MERTOĞLU, HATİCE (My University, 2023)
In this research, it is aimed to investigate the relationship between nutritional literacy and healthy lifestyle behaviors of prospective teachers according to various variables. Correlational survey model of the quantitative research methods is used in this survey. A moderate positive relationship was found between prospective teachers’ nutritional literacy and healthy lifestyle behaviors. Based on the positive relationship between nutritional literacy and healthy lifestyle behaviors, it is recommended that nutritional literacy level be associated with healthy lifestyle by giving nutrition education at all school levels and undergraduate education in order to increase the level of healthy lifestyle behaviors in individuals.
Keywords: Temel Bilimler; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary; College Students; Correlational Survey; Healthy Lifestyle; Nutritional Literacy